Eugenol-rich Fraction of Syzygium aromaticum (Clove) Reverses Biochemical and Histopathological Changes in Liver Cirrhosis and Inhibits Hepatic Cell Proliferation - Ali, Shakir (J Cancer Prev, 2014)
BACKGROUND: Dried flower bud of Syzygium aromaticum (clove) is rich in eugenol, an antioxidant and antiinflammatory compound that can protect liver against injury. Clove, besides eugenol, also contains other pharmacologically active phytochemicals such as β-sitosterol and ascorbic acid. This study reports the effect of eugenol-rich fraction (ERF) of clove on liver cirrhosis induced by thioacetamide. METHODS: Cirrhosis of the liver, which predisposes to hepatocellular carcinoma, was induced by administering thioacetamide (0.03%) in drinking water for 16 weeks. Cirrhotic animals were divided into two groups; the treated group was administered ERF for 9 weeks, one week after discontinuation of thioacetamide, while the other group received normal saline for a similar duration of time. RESULTS: The treatment with ERF, as determined by histopathology and through a battery of biochemical markers of hepatic injury, oxidative stress and drug metabolizing enzymes, significantly ameliorated the signs of liver cirrhosis. It lowered the elevated levels of alkaline phosphatase, γ-glutamyl transferase and other biochemical changes in liver cirrhosis. Histopathology of the liver corroborated the effect of ERF with biochemical findings. ERF treatment further inhibited cell proliferation, as demonstrated by reduced [(3)H]-thymidine uptake. CONCLUSIONS: Data provide evidence supporting the protective action of ERF on liver cirrhosis. The study assumes significance because cirrhosis predisposes the liver to cancer, which is characterized by abnormal cell proliferation. ERF in this study is reported to inhibit hepatic cell proliferation and at the same time decrease oxidative stress, which might be the mechanism of protection against liver cirrhosis.